1994
DOI: 10.1128/aac.38.3.499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fat- and calcium-rich breakfast on pharmacokinetics of fleroxacin administered in single and multiple doses

Abstract: The effect of a fat-and liquid-calcium-rich meal on the pharmacokinetics of single and multiple doses of fleroxacin in 20 healthy men and women was investigated in a randomized crossover fashion. Fleroxacin was administered as 400 mg daily for 3 days and as a single 400 mg dose. Concurrent administration of fleroxacin with food resulted in a statistically significant (P c 0.05) decrease in the area under the curve (13.9%Yo for multiple-dose administration, 10% for single-dose administration) and in the peak co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Frost et al [14] studied the effect of a high fat/high calcium breakfast, containing 729 mg of calcium, on the absorption of ciprofloxacin and found no significant differences in any of the pharmacokinetic parameters. In contrast, Bertino et al [10] found that the absorption of fleroxacin was decreased 10% (P < 0.05) by concomitant ingestion of a breakfast containing 393 mg of calcium [10].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Frost et al [14] studied the effect of a high fat/high calcium breakfast, containing 729 mg of calcium, on the absorption of ciprofloxacin and found no significant differences in any of the pharmacokinetic parameters. In contrast, Bertino et al [10] found that the absorption of fleroxacin was decreased 10% (P < 0.05) by concomitant ingestion of a breakfast containing 393 mg of calcium [10].…”
Section: Resultsmentioning
confidence: 90%
“…The inter-day coefficients of variation for the control samples were 3.6% (mean, 0.29 jg ml-; n = 9) and 2.9% (mean, 1.7 jig ml-; n = 9). [10] found that the absorption of fleroxacin was decreased 10% (P < 0.05) by concomitant ingestion of a breakfast containing 393 mg of calcium [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the interaction between the fluoroquinolones such as norfloxacin [7,17], ofloxacin [15,17], ciprofloxacin [3-6, 9, 10], lomefloxacin [11,16], DR-3355 (levofloxacin) [12] and fleroxacin [14,18] and cations has been reported. Shimada et al [19] studied the effect of antacid (dried aluminum hydroxide gel) on sparfloxacin gastrointestinal absorption, and found that it was the least inhibited by interaction with an antacid, compared with other new quinolones.…”
mentioning
confidence: 99%
“…[7,17], ofloxacin [15,17], ciprofloxacin [3-6, 9, 10], lomefloxacin [11,16], DR-3355 (levofloxacin) [12], fleroxacin [14,18], and sparfloxacin [19][20][21][22][23] is decreased by concomitant administration of metal cation containing drugs. Therefore, the interaction between sparfloxacin and sucralfate can be explained primarily by the inhibition of absorption of sparfloxacin.…”
mentioning
confidence: 99%